Variation Saisonnière De La Qualité Physico-Chimique Des Eaux Souterraines Des Aquifères d’Altérites Du Département d’Agboville (Sud-Est De La Côte d’Ivoire) - Orou, Rodrigue Kotchi; Soro, Gbombélé; Soro, Drissa Tanina; Fossou, Rosine Marie N’guessan; Onetie, Oscar Zahibo; Ahoussi, Ernest Kouassi; Soro, Nagnin (European Scientific Journal, ESJ, 2016)
The main objective of this study was to evaluate the seasonal quality to explain the phenomena at the origin of the mineralization of groundwater in the department of Agboville. Hydrochemical analysis was performed in 24 wells located throughout the study area. Hydrochemical different methods and techniques of multivariate statistical analysis were used to study these waters. The physicochemical analyzes show that the water is acidic with an average pH of 6.09 in the rainy season and 6.29 in the dry season. Overall, these waters are soft and slightly mineralized with an average electrical conductivity of 172.92 μS / cm in the rainy season and 196.71 μS / cm in the dry season. These waters are mineralized in the dry season than rainy. The hydrochemical classification of water from the Piper diagram showed one hydrofacies is calcium chloride-facies. Quality chemical parameters are mostly below the WHO (2011) guideline values, except for some points (29.17%) where levels of nitrites and ammonium sometimes exceed the guide values. The various processes responsible for the acquisition of the chemistry of groundwater are studied: the residence time of water in contact with the host rock, the redox infiltration of substances linked to human activities and litter decomposition. In the mineralization mechanisms, hydrolysis of silicates is the dominant process.